Strategi Memanfaatkan Media Sosial dalam Meningkatkan Kepribadian Siswa di SMA Perspektif Pendidikan Islam - Halik, Abdul; Hanafie, St Wardah; Taufan, Erna Rasyid; Naim, Muh (Al-Ulum, 2024)
The purpose of this research is to find strategies for using social media that are effective in improving the personality of students from an Islamic education perspective. The research method used is qualitative, descriptive in nature, with a phenomenological model. The research was conducted on students at SMAN 3 Parepare. Research resultThe use of social media among students is to establish interaction with fellow friends and also with teachers, apart from that social media is sometimes used in the learning process while online learning is carried out. Furthermore, social media is also used by students to search for literature to add insight. has implications for the personality of students, both positive and negative, while the positive implications include, making students more creative in completing assignments given, students can participate in discussions conducted through social media. With this, students will become independent individuals, easily adaptable to socializing with others and able to manage friendship networks.